Предмет: Математика,
автор: DachaKim
- (4,1x + 2,5) - (2,3x + 3,9) = 1,6x
Ответы
Автор ответа:
0
- (4,1x + 2,5) - (2,3x + 3,9) = 1,6x
-4,1х-2,5 -2,3х-3,9-1,6х=0
-8х-6,4=0
-8х=6,4
х=6,4:(-8)
х=--0,8
-4,1х-2,5 -2,3х-3,9-1,6х=0
-8х-6,4=0
-8х=6,4
х=6,4:(-8)
х=--0,8
Автор ответа:
0
- (4,1x + 2,5) - (2,3x + 3,9) = 1,6x
-4,1х - 2,5 - 2,3х - 3,9 = 1,6х
-8х = 6,4
х= -0,8
-4,1х - 2,5 - 2,3х - 3,9 = 1,6х
-8х = 6,4
х= -0,8
Похожие вопросы
Предмет: Математика,
автор: mirabuan89
Предмет: Алгебра,
автор: lololoska238
Предмет: Алгебра,
автор: mastitskayayulia
Предмет: Обществознание,
автор: SERSHANT